Best Answer

7 feet 9 inches - 2 feet 11 inches = 4 feet 10 inches.

Q: What is 7 feet 9 inches minus 2 feet 11 inches?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

4.79 feet

13 feet, 2 inches 42 feet 11 inches - 29 feet 09 inches = 13 feet 02 inches

35 inches, or 2 feet 11 inches.

multiply feet by 12 and add inches; then minus inches. Example: 2 feet 2 inches minus 5 inches = 26-5 = 21 inches

1 Foot 11 Inches

Related questions

2 feet and 3 inches.

4.79 feet

13 feet, 2 inches 42 feet 11 inches - 29 feet 09 inches = 13 feet 02 inches

35 inches, or 2 feet 11 inches.

multiply feet by 12 and add inches; then minus inches. Example: 2 feet 2 inches minus 5 inches = 26-5 = 21 inches

7 feet 3 inches.

11 ft - 8 ft = 3 ft - 1 ft = 2 ft 12 + 2 = 14 - 6 = 8 inches answer is 2 feet 8 inches

(8 feet 0 inches) minus (2 feet 5 inches) = 5 feet 7 inches.

1 Foot 11 Inches

yup it is 2 feet 5 inches

Make your 6'9" into 5'21" Then subtract your feet (5'-2'=3') and next subtract your inches (21"-11"=10") For the final answer, join your intermediate answers together: 3'10"

5 feet minus 2 in a half inches, also known as 4 feet 9.5 inches is equal to 1,460.5 millimeters.